Effect of microstructure on plain strain fracture toughness of carbon steel - Muhamad Hanif, Muhamad (2012)
This project is about to study the effect of microstructure on plain strain fracture toughness of carbon steel. The objectives for this project are to study the effect of microstructure on plain strain fracture toughness of carbon steel and to study the effect of transformation structure on fracture toughness (K1C). This project involves preparation 26 specimens of low carbon steel which is the mild steel. Two notch diameters (5.6 mm and 4.2 mm) and two notch angles (α) namely 60° and 80° have been used to observe the fracture toughness of the steel. By full annealing heat treatments process, it can used to differentiate the microstructure of the steel and its effect on the fracture toughness is also observed. Mounting process is done for two of the specimen before observation of the microstructure using Optical Microscope. The tensile test done and the fracture toughness can be getting from the calculation. It has been found that the heat treatment specimens are softer and brittle but for the no heat treatment specimens it is stronger and harder. Fine grained structure improved fracture toughness. Higher notch angles give lower fracture toughness and lower notch diameter gives lower fracture load. For 60° angle, lower notch diameter give higher fracture toughness. For 80° angle, lower notch diameter give lower fracture toughness. Microstructure of steel has the strong influence on the value of K1C. The finer grain structure has been found to have higher value of K1C than a coarse and wider grained structure. Non heat treated samples are stronger and harder but for the heat treatmeent sample it is softer and brittle.